2005
DOI: 10.1080/09553000500143534
|View full text |Cite
|
Sign up to set email alerts
|

L5178Y sublines: a look back from 40 years. Part 2: Response to ionizing radiation

Abstract: The aim was to review and summarize the results of 40 years of study concerning the response to ionizing radiation of the pair of L5178Y (LY) sublines, LY-R and LY-S, that differ in sensitivity to various DNA-damaging agents, among them X- and gamma-rays. The reviewed data indicate the key importance of DNA damage repair and fixation for the ultimate fate of the irradiated LY cell. The cause of slow double-strand break (DSB) repair in LY-S cells is not identified, but a defect in non-homologous end-joining (NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The mechanism responsible for differences in telomere length between L5178Y cell lines is unclear (Szumiel 2005). Both L5178Y-R and L5178Y-S cells express telomerase (McIlrath et al 2001), but extended growth in culture showed little change in average telomere length, indicating that a telomere length equilibrium had been reached (Sprung et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism responsible for differences in telomere length between L5178Y cell lines is unclear (Szumiel 2005). Both L5178Y-R and L5178Y-S cells express telomerase (McIlrath et al 2001), but extended growth in culture showed little change in average telomere length, indicating that a telomere length equilibrium had been reached (Sprung et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…40–50 kb [13,14]. In contrast, LY-S cells show IR sensitivity [15] and have much shorter telomeres which are in the region of ~ 7 kb. A recent study indicates that this pair of cell lines may have different telomere lengths in different laboratories [16].…”
Section: Resultsmentioning
confidence: 99%
“…This conversion also involves alterations in cell sensitivity to other physical factors, such as ultraviolet light, hydrogen peroxide, and short exposure to heat, and has been thoroughly reviewed by Szumiel (5,6). It has been proven that loss of tumorigenicity in LY-R cells is related to lack of expression of a single tumor antigen in their surface, a 64-kDa membrane glycoprotein, which is affected by the source of fetal serum supplemented to the culture medium, since only LY-R cultured in media supplemented with fetal horse serum, but not fetal calf serum, conserved their tumorigenic properties in vivo (4).…”
Section: Introductionmentioning
confidence: 99%